Biofilm formation of Salmonella enterica and the central role of rpos sigma factor in stress resistance - Wan Zawiah Wan Abdullah,; Mackey, Bernard M.; Karatzas, Kimon-Andreas G. (Penerbit Universiti Kebangsaan Malaysia, 2017)
Non-typhoidal Salmonella is considered as the leading cause of foodborne illness and it has been associated with highprofile outbreaks in many groups of foods. This work examines the contribution of phenotypic properties related to survival (biofilm formation) and how these are linked with the genetic and functional variability of rpoS gene and RpoS status respectively in Salmonella enterica. The test strains were Salmonella serovars Anatum, Enteritidis (466), Enteritidis (496), Hadar, Heidelberg, Montevideo, Newport and Virchow and two Typhimurium strains previously characterised as either RpoSpositive or RpoS-negative. RpoS status was found to affect biofilm formation. The capability of Salmonella to resist stress and survive under unfavourable conditions can vary between strains. We confirmed that the two strains that were previously sensitive to various stresses harboured significant mutations in the rpoS gene. The rpoS sequencing not only confirmed a link between RpoS and biofilm formation, but it also revealed a link with differences in the utilisation of carbon sources. The RpoS-negative phenotype was linked with an increased growth under different carbon sources suggesting that a functional RpoS is a burden for growth which is in agreement with the SPANC hypothesis.